Applying Universal Principles of ‘Best Interest’: Practice Challenges across Transnational Jurisdictions, Cultural Norms, and Values - Brian Littlechild; Carolyn Housman (Children, 2023)
This article sets out key issues in determining and upholding the best interests of children, in need of social service support, who have family networks that span outside of the UK. These issues are then analysed against whether and how child protection professionals take these into account along with an overall consideration of the United Nations Convention on the Rights of the Child’s (UNCRC) ‘best interests of the child’, when assessing and planning for those needs in kinship care cases. Building on these themes, the findings of an exploratory study on international kinship care cases carried out by Children and Families Across Borders (CFAB), the UK branch of the non-governmental organisation, International Social Service, as well as CFAB’s associated Freedom of Information Requests to the UK government, are examined. These are then analysed in relation to legal and policy documents in England. Agency case records are analysed to identify a range of factors for children placed with ‘kinship’ carers across national borders, relating to the cultural relativity of the ‘best interest’ principle, the availability of family support in different social service structures, the understanding and application of legislation and policy in transnational contexts, and the availability of markers to track and analyse the scale of children crossing borders to join family.